"Itak Gurgur" and its Meaning in the Batak Cultural Community - Manalu, Hery Buha (LANCAH: Jurnal Inovasi dan Tren, 2024)
The emphasis of this research is ethics awareness that places humans in balance with their natural environment. Batak culture which is inseparable from nature (the cosmos) has also cultivated the tradition of eating "Itak Gurgur" as a value of human togetherness and balance, universe and God. There is a message of the value of simplicity, honesty and balance in this tradition. Three things to eat "Itak Gurgur" as a prayer for caring for togetherness, a sacred intention for blessings and prosperity, ideals ("sada tahi"). "Itak" is rice flour that is pounded or ground into a soft, white color ("puti") as a meaning of purity and prayer to Mula Jadi (the Greatest). "Itak" diadone of coconut, palm sugar and salt, clenched into a fist, a symbol of the tenacity of burning unity. To remain in harmony with the values of unity, in natural balance. unite the agreement ("sada tahi") then comes the spirit, the burning enthusiasm to achieve success. the spirit of eating "Itak Gurgur" together brings "Omo pariama" abundant harvest and gratitude. Constructing cultural theology, eating, "Itak Gurgur" as a Batak "local sacrament", reminding the balance of life between: Humans, God and the Universe.